Speech Intelligibility in (3-4 Years Old) Typically Developing Children - Shishira S.Bharadwaj; Sushma S.; Sreedevi N. (Journal of All India Institute of Speech and Hearing, 1970)
Speech intelligibility is an index of overall speech adequacy. It reflects the child's verbal communication competence and is vital in determining the need for intervention. Intelligibility data for young children with typical as well as disordered phonologies are lacking, even though they are critical for clinical decisions. The present study aimed at tracking the developmental progress in speech intelligibility with increasing age in two tasks: spontaneous speech and sentence imitation. The study included 16 kindergarten (3-4 years) typically developing Kannada speaking children as participants who were divided into four age groups: a) 3-3.3years b) 3.3- 3.6 years c) 3.6-3.9 years d) 3.9-3.12 years. The speech samples were recorded using a digital recorder. These were played to 12 unfamiliar and untrained adults within 35 years of age who served as the judges for the study. Three judges were assigned to each age group and were played the first hundred utterances of the spontaneous speech and sentence imitation samples for verbatim transcription. The verbatim transcription of each subject was evaluated and percent speech intelligibility was obtained using the key developed by the researcher for each subject's utterances per se. Mean, standard deviation and range of percent intelligibility were obtained for each age group and for the two tasks separately. Appropriate statistical analysis was carried out using SPSS package, the results revealed a statistically significant difference across the age groups for spontaneous speech task and not for the sentence imitation task. However, there was no significant difference across the two tasks. The study indicated a linear progress in intelligibility with increasing age especially in spontaneous speech. The findings show that, by 3.3 years, normal children achieve 85% intelligibility and near 100% intelligibility by four years of age itself. This finding has important clinical significance for assessment of intelligibility in children with communication disorders.